Comparison of the Cockroft–Gault, simplified Modification of Diet in Renal Disease, and Chronic Kidney Disease Epidemiology Collaboration formulas in the determination of chronic kidney disease advancement - Szeliga-Król, Jolanta; Zubilewicz, Renata; Panasiuk-Kamińska, Katarzyna; Załuska, Wojciech; Urbańczuk, Marcin; Jaroszyński, Andrzej (Family Medicine & Primary Care Review, 2016)
Background . Chronic kidney disease (CKD) is at present a worldwide health problem. According to the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF KDOQI), chronic kidney disease has five stages of advancement based on the estimated glomerular filtration rate (eGFR). The formulas that are most frequently used in determining eGFR are the Cockroft–Gault (CG ) formula, the simplified Modification of Diet in Renal Disease (MDRD ) formula, and the Chronic Kidney Disease Epidemiology (CKD-EPI) Collaboration formula, which is considered the most accurate formula. Objectives . The aim of our study was to compare the CG, simplified MDRD and CKD-EPI formulas for determining eGFR and thus CKD advancement. Material and methods. The study was conducted on a group of 202 patients with previously diagnosed CKD. To calculate the eGFR, the CG, simplified MDRD, and CKD-EPI formulas were used. Patients were assigned a disease stage (from 1 to 5) according to the NKF KDOQI guidelines. Results . The calculated eGFR values varied depending on the formula, which resulted different assignations of patients to CKD stages. The largest difference regarded the qualification of the patients to the first and the fifth stage. A similar number of patients were classed as stage three by all formulas. Differences were also seen in how the formulas classified patients to the second and fourth stages. Conclusions . GFR estimation remains a problematic clinical concern. The CKD stage assigned to patients varies depending on the formula used, a fact which may be particularly significant for general practitioners. Laboratories should apply the CKD-EPI formula for eGFR calculation, as it gives the least false results.